Controllable preparation of anatase TiO2 nano arrays on Ti foil for flexible dye-sensitised solar cells. (May 2015) - Liu, W. W.; Lu, H.; Wang, H.Y.; Zhang, M.; Guo, M.
<x content-type="archive" xml:space="preserve">Abstract</x> Flexible dye-sensitised solar cells (DSSCs) have been attracting considerable attention because of its flexibility and lightweight. In this study, TiO2 nano arrays with different morphologies were successfully synthesised on Ti foil via hydrothermal process. The effects of preparing conditions such as concentration of NaOH solution, hydrothermal temperature, reaction time and the additive NaCl on the formation of TiO2 nano arrays were systematically investigated by X-ray diffraction, scanning electron microscopy and photovoltaic tests. The growth mechanisms of nano arrays with different morphologies were also discussed. Moreover, the as-prepared TiO2 nanosheets array film was used as a photoanode of the flexible DSSC, a power conversion efficiency of 1.88% was obtained.